Odpowiedzi

2010-01-09T14:25:59+01:00
X-y=0 => x=y
x+y+z=4 =>2y = 4-z
x+2y+3z=9 => y + 4-z + 3z = 9
y + 2z = 5

2y = 4-z
y = 5-2z

2(5-2z)=4-z
10 - 4z = 4-z
6 = 3z / :3
z = 2

y = 5-2z
z=2

y = 5 - 4
y=1

x=y=1
z=2
2010-01-09T14:27:40+01:00
X-y = 0 ---> x = y
x+x + z = 4
x + 2x + 3z = 9
---------------------
2x +z = 4 , mnożę obustronnie przez -3
3x + 3z = 9
x=y
---------------------
-6x -3z = -12
3x + 3z = 9
x = y
---------------------
dodaję stronami równania
-3x = -3
x = y
---------------
x = 1
y = 1
z = 4 - 2x = 4 -2 = 2